An Analysis of the Use of Religious Values in Commercial Advertising: A Da'wah and Communication Approach Based on Charles Sanders Peirce's Theory - Indriyani, Putri Isma (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2024)
This study analyzes the commodification of religious values in the advertising world with reference to the theory of Charles Sanders Peirce. Religious values are often used as marketing tools to influence consumer perceptions and behaviors. The aim of this study is to understand how religious values are transformed into commodities in advertisements and how this is reflected in Peirce's theory of signs and meaning. This research employs a qualitative approach by analyzing advertisements that utilize religious value elements as their main attraction. The results of the analysis show that these advertisements employ commodification strategies by transforming the meaning of religious values into something that can be traded and consumed. The implication is the importance of critiquing advertising practices that use religious values for commercialization purposes. This study contributes to understanding the dynamics of commodifying religious values and its influence on consumer society in the context of modern advertising.